2019
DOI: 10.5696/2156-9614-9.23.190905
|View full text |Cite
|
Sign up to set email alerts
|

Continued Medical Waste Exposure of Recyclable Collectors Despite Dumpsite Closures in Brazil

Abstract: Background. Brasilia, the capital of Brazil, currently has the largest dumpsite of the Americas at Estrutural, with over 30 million tons of waste accumulated. Recyclable waste collectors are a group of workers who, in addition to having a low socioeconomic status and residing in vulnerable areas, work sorting garbage in inadequate and unsanitary areas. This profession puts individuals at risk, resulting in death, mutilation, and disease for workers. Objectives. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
0
7
0
4
Order By: Relevance
“…vulnerability contexts (21) . For example, a qualitative study carried out with associated women waste pickers showed that they had life trajectories marked by economic, family, and social vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…vulnerability contexts (21) . For example, a qualitative study carried out with associated women waste pickers showed that they had life trajectories marked by economic, family, and social vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning occupational diseases, there is evidence of the high incidence of musculoskeletal disorders, chronic non-communicable diseases (arterial hypertension and diabetes mellitus), infectious diseases, verminous diseases, and allergic diseases in this population. Long working hours, combined with lack of access or non-use of personal protective equipment, aggravate the risk of illness at work (7,9,21) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such injuries are comprised head, hands, arms legs, and feet burns and cuts, lesions of eyes and skin, and even hand amputations. [29] Another study in Egypt also indicated the prevalence of HBV among dumpsite workers, emphasizing on the necessity for vaccination as a prophylactic measure. [30] Studies are still conducted in Nigeria, where workers were exposed to hazardous substances, which might cause a variety of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas small numbers of informal waste workers are known to purposefully seek medical waste as a valuable resource to be reused or recycled, waste pickers also encounter medical waste accidentally while searching for other valuable materials (Zolnikov et al, 2019).…”
Section: Sharps and Needlestick Injuries To Informal Waste Collectorsmentioning
confidence: 99%